An RNAi-Based Candidate Screen for Modifiers of the CHD1 Chromatin Remodeler and Assembly Factor in Drosophila melanogaster. - Kim, S.; Bugga, L.; Hong, E.S.; Zabinsky, R.; Edwards, R.G.; Deodhar, P.A.; Armstrong, J.A. (G3 : genes - genomes - genetics, 2015)
The conserved chromatin remodeling and assembly factor CHD1 (chromodomains, helicase, DNA-binding domain) is present at active genes where it participates in histone turnover and recycling during transcription. In order to gain a more complete understanding of the mechanism of action of CHD1 during development, we created a novel genetic assay in Drosophila melanogaster to evaluate potential functional interactions between CHD1 and other chromatin factors. We found that overexpression of CHD1 results in defects in wing development and utilized this fully penetrant and reliable phenotype to conduct a small-scale RNAi-based candidate screen to identify genes that functionally interact with chd1 in vivo. Our results indicate that CHD1 may act in opposition to other remodeling factors, including INO80, and that the recruitment of CHD1 to active genes by RTF1 is conserved in flies.